Human Amniotic Fluid Stem Cells as an Attractive Tool for Clinical Applications - Trohatou, Ourania; P. Anagnou, Nicholas; G. Roubelakis, Maria (Current Stem Cell Research & Therapy, 2013)
Recent studies support cell based therapies for several diseases. Human fetal stem cells have received much attention for developing new therapeutic strategies. Recently, our group and others have successfully isolated and expanded karyotypically normal stem cells from an alternative fetal source, the human second trimester amniotic fluid (AF) and performed a systematic phenotypic and molecular analysis. The main characteristics of amniotic fluid stem cells (hAFSCs) are their fetal origin, the high number of isolated cells, their wide differentiation properties and their rapid expansion in vitro. These characteristics render hAFSCs as a very attractive tool for clinical applications based on cell therapy. The use of hAFSC transplantation has been studied in a variety of disease animal models related to bone regeneration, myocardial infarction, acute kidney injury, acute hepatic failure, skin injury, ischemic hind limb or cancer. The major aim of this review is to summarize the advent of hAFSCs capabilities into novel therapeutic modalities and discuss their potential use in future pre-clinical and clinical studies.
Keywords: IMMUNOMODULATORY PROPERTIES